2013
DOI: 10.2147/jn.s43712
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the clinical effects of cell therapy for thoracolumbar spinal cord injury: an original study

Abstract: Background: Cell therapy is amongst the most promising treatment strategies in spinal cord injury (SCI) because it focuses on repair. There are many published animal studies and a few human trials showing remarkable results with various cell types. The level of SCI determines whether paraplegia or quadriplegia is present, and greatly influences recovery. The purpose of this study was to determine the significance of the clinical effects and long-term safety of intrathecal administration of autologous bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…On comparing the results of the current study on cervical SCI patients with our previously published data on thoracolumbar SCI [28], we found that the effect of cell transplantation was better in the thoracolumbar SCI group. Hence, the neurological and functional outcome also depends on the level of injury along with other factors of SCI.…”
Section: Discussionsupporting
confidence: 49%
“…On comparing the results of the current study on cervical SCI patients with our previously published data on thoracolumbar SCI [28], we found that the effect of cell transplantation was better in the thoracolumbar SCI group. Hence, the neurological and functional outcome also depends on the level of injury along with other factors of SCI.…”
Section: Discussionsupporting
confidence: 49%
“…It has gained popularity in the management of various neurological disorders such as ALS, stroke, Alzheimer, spinal cord injury, and TBI [15][16][17][18][19]. Preclinical studies [9][10][11] have used various types of stem cells and different routes of administration in the treatment of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Their safety and efficacy has already been established in other neurological disorders. [19][20][21][22][23][24][25][26] These cells are a mixture of various hematopoietic and non hematopoietic cells which are more potent in combination as compared to their individual fractions. On transplantation, they migrate to the damaged areas and initiate repair.…”
Section: Discussionmentioning
confidence: 99%